Managerial incentives in an entrepreneurial stock market model - Kihlstrom, Richard E; Matthews, Steven A (Journal of Financial Intermediation, 1990)
This paper addresses the First Theorem of Welfare Economics in a moral hazard environment. An entrepreneur sells equity in a firm which he supplies with an unobservable, costly input. How much equity he retains determines his incentives and is observed by investors. The investors have rational expectaions which cause the equity price to increase in the amount of equity the entrepreneur retains. This gives the entrepreneur an incentive to retain equity and hence supply input. The entrepreneur may also be bound by an explicit incentive contract. In this framework, not all competitive equilibria are efficient, as defined relative to the moral hazard constraint. However, equilibria can be inefficient only if the entrepreneur's optimal input is nonunique or exhibits positive income effects.